Metabolic engineering with Dof1 transcription factor in plants: Improved nitrogen assimilation and growth under low-nitrogen conditions - Yanagisawa, Shuichi (National Academy of Sciences, 2004)
Utilization of transcription factors might be a powerful approach to modification of metabolism for a generation of crops having superior characteristics because a single transcription factor frequently regulates coordinated expression of a set of key genes for respective pathways. Here, we apply the plant-specific Dof1 transcription factor to improve nitrogen assimilation, the essential metabolism including the primary assimilation of ammonia to carbon skeletons to biosynthesize amino acids and other organic compounds involving nitrogen in plants. Expressing Dof1 induced the up-regulation of genes encoding enzymes for carbon skeleton production, a marked increase of amino acid contents, and a reduction of the glucose level in transgenic Arabidopsis. The results suggest cooperative modification of carbon and nitrogen metabolisms on the basis of their intimate link. Furthermore, elementary analysis revealed that the nitrogen content increased in the Dof1 transgenic plants (≈30%), indicating promotion of net nitrogen assimilation. Most significantly, the Dof1 transgenic plants exhibit improved growth under low-nitrogen conditions, an agronomically important trait. These results highlight the great utility of transcription factors in engineering metabolism in plants.